Body memory and kinesthetic body feedback: The impact of light versus strong movement qualities on affect and cognition - Koch, Sabine C.; Fuchs, Thomas; Summa, Michela (Memory studies, 2014)
What influence does body memory from light vs strong movement qualities have on affect and cognition? This article relates the phenomenological theory of body memory, movement observation theory from dance, and psychological conceptual and empirical work on body feedback. Kinesthetic body feedback means efferent feedback from the body’s peripheral movements to the higher cortical functions, such as the systematic effects of the adoption of certain gestures or postures on the memory for life events. Meaning of movements is stored in the body in relation to our learning history –ontogenetic as well as phylogenetic. Based on the phenomenological theory of body memory, we hypothesize that specific movement qualities will have a differential impact on affect and cognition. In accordance with our hypotheses, our results suggest that strong movements are related to more fighting affect and more negative memory recall, whereas light movements – just as a non-movement control condition – are related to more indulgent affect and more positive memory recall. Results are discussed with reference to the phenomenological framework.
Gesehen am 29.09.2020